Standardization of BIM Execution Plans (BEP’s) for Mega Construction Projects; A Comparative and Scientometric Study - Shawky, Kamal Ahmed; Abdelalim, Ahmed Mohammed; Sherif, Alaa Gamal (Transactions on Engineering and Computing Sciences, 2024)
Building Information Modeling (BIM) is the foundation of the Architecture, Engineering, and Construction (AEC) industry’s digital transformation. BIM is a method of creating and managing information on a construction project over its entire life cycle. The lack of standardized processes for developing Building Execution Plans (BEPs) is a significant impediment. This paper presents a comprehensive review of the development and implementation of BEPs in AEC industry. The purpose of the study is to identify and analyze the content topics of a BEP. The paper highlights the prevalence of differences in the content, structure, practice methods, contractual requirements, and project characteristics among various BIM execution planning guidelines. It also identifies the need for standardized approaches to information exchange and collaboration in BIM projects. The findings of this research provide insights for industry professionals, researchers, and technology developers interested in the current and future uses of BEPs and smart document application in BIM. This study identified and analyzed 36 BEP documents published by diverse organizations globally. Results showed a theoretical framework shared among most BEPs, despite variations in content presentation and chapter titles. The identified key elements in BEPs include project information, goals and objectives, roles and responsibilities, collaboration procedures, model structure, quality control, technology infrastructure needs, and project deliverables. Furthermore, the study proposes a comprehensive BEP framework, synthesized from the most frequently occurring sub-elements in the analyzed documents. This study conducts a thorough Scientometric analysis using the Web of Science and Scopus databases to examine the development of scientific trends and subjects in the realm of BIM Execution Plans from 2020 to 2023 as it’s the most period has Development in BEP. The lack of standardized guidelines for BEP development is identified as a significant impediment, leading to inconsistencies and inefficiencies in project delivery.